Spiritual care perceptions and empathy of Chinese nursing students: The mediating roles of spiritual well-being. Issue 5 (October 2022) - Wang, Zhangyi; Liang, Yuan; Zhao, Haomei; Zhu, Yue; Liu, Mengru; Zhang, Yajun; Xiao, Luwei; Piao, Jingjing; Zhao, Xiqun; Liu, Zhijian; Liu, Li; Pang, Xiaoli; et al.
Abstract: Objective: To investigate spiritual care perceptions, spiritual well-being, and empathy, examine the correlations among spiritual care perceptions, spiritual well-being, and empathy, and explore the mediating role of spiritual well-being between other two variables of Chinese nursing students. Methods: A cross-sectional design was implemented, and the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) Checklist was used to ensure quality reporting of the study. A cluster sample of 2, 718 nursing students was selected from 7 universities and colleges in China. The demographic characteristics questionnaire, the Chinese Version of the Spiritual Care-Giving Scale (C-SCGS), the Spiritual Health Scale Short Form (SHS-SF), and the Jefferson Scale of Physician Empathy-Nursing Student (JSPE-NS) were used. Descriptive statistics, correlation, and process plug-in mediation effect analyses were used to analyze the data. Results: The total score of spiritual care perceptions, spiritual well-being, and empathy were 173.83 ± 25.62, 98.74 ± 12.87, and 105.04 ± 21.34, respectively. Spiritual care perceptions were positively correlated with spiritual well-being ( r = 0.617, p < 0.01) and empathy ( r = 0.528, p < 0.01). And spiritual well-being played a partial mediating role between the other two variables (accounting for 28.1%). Significance of results: Spiritual care perceptions, spiritual well-being, and empathy were quite moderate, which need in improving. It is suggested that nursing educators pay attention to the spiritual care education of nursing students, perfect the spiritual care education system, and take targeted measures according to nursing students' individual personality traits and differences, improve their spiritual well-being and empathy in multiple ways, so as to improve their spiritual care perceptions and competence.